2020
DOI: 10.1002/1873-3468.13798
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the regulators: role of phosphorylation in modulating the function of the GBF1/BIG family of Sec7 ARF‐GEFs

Abstract: Membrane traffic between secretory and endosomal compartments is vesiclemediated and must be tightly balanced to maintain a physiological compartment size. Vesicle formation is initiated by guanine nucleotide exchange factors (GEFs) that activate the ARF family of small GTPases. Regulatory mechanisms, including reversible phosphorylation, allow ARF-GEFs to support vesicle formation only at the right time and place in response to cellular needs. Here, we review current knowledge of how the Golgi-specific brefel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…The ubiquitous function of Arf1 is mediated by its activation through specific GEFs (Guanine exchange factors). For instance, GBF1 (Golgi-specific brefeldin A-resistance guanine nucleotide exchange factor 1) localizes to the cis -medial Golgi and regulates COPI vesicle assembly through Arf1 (Garcia-Mata et al, 2003; Kawamoto et al, 2002; Manolea et al, 2008); BIG1 and BIG2 (Brefeldin A-inhibited guanine nucleotide exchange proteins) localize to the late Golgi and regulate the membrane traffic between TGN and endosomes (Ishizaki et al, 2008; Manolea et al, 2008; Walton et al, 2020). Hence, Arf1 function can be selectively inhibited by specific inhibition of Arf1-GEFs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ubiquitous function of Arf1 is mediated by its activation through specific GEFs (Guanine exchange factors). For instance, GBF1 (Golgi-specific brefeldin A-resistance guanine nucleotide exchange factor 1) localizes to the cis -medial Golgi and regulates COPI vesicle assembly through Arf1 (Garcia-Mata et al, 2003; Kawamoto et al, 2002; Manolea et al, 2008); BIG1 and BIG2 (Brefeldin A-inhibited guanine nucleotide exchange proteins) localize to the late Golgi and regulate the membrane traffic between TGN and endosomes (Ishizaki et al, 2008; Manolea et al, 2008; Walton et al, 2020). Hence, Arf1 function can be selectively inhibited by specific inhibition of Arf1-GEFs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In light of our new findings, several observations reconcile the previous interpretations and provide additional support for our structural model of Sec7 autoregulation. Constructs used previously to test the function of the HDS1 domain (13, 54, 55) considered the GEF-HDS1 linker to be part of the HDS1 domain. We now know that these linker residues serve to position the GEF domain relative to the DCB-HUS domain in both the Gea2 cryo-EM structure(19) and the predicted active conformation of Sec7 (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These differential effects of ZCL-278 and BFA indicated that DAPG-mediated changes of sAPPα and Aβ levels were at least partly independent. BFA inhibits ADP-ribosylation factors–guanine–nucleotide–exchange factor (ARF-GEFs) including Golgi-specific brefeldin-resistance factor a (GBF1) and BFA-inhibited guanine nucleotide exchange protein 1 and 2 (BIG1 and BIG2) [ 39 , 40 , 41 ]. Compared with BFA, GCA is a relatively specific inhibitor of GBF1 but not BIG1/2 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This differential localization likely results in the distinct roles of the ARF-GEFs and their inhibitors [ 33 , 40 ]. Furthermore, BIG2 is also associated with recycling endosomes, an organelle other than the Golgi complex [ 39 , 41 ], and BFA also disrupts sorting pathways in the endosomal system [ 39 , 42 ]. These reports suggest that BFA effects in DAPG-treated 293sw cells depended on BIG1, BIG2, or endosomal trafficking, but not on GBF1 or the cis-Golgi compartment.…”
Section: Discussionmentioning
confidence: 99%